Agroenergy and Agriculture (Revista de Ciências Agroveterinárias, 2010)
Global warming is attributed mainly to the indiscriminate burning of oil which releases large amounts of greenhouse gases in the atmosphere. This encouraged the search for alternative energy sources, including the use of biofuels, such as ethanol and biodiesel. The purpose of this review is to discuss the impacts of biofuel production on Brazilian and world agricultural activity. In order to analyze the feasibility of replacing oil for biofuels, in addition to the technical and economic aspects, it is important to take into account environmental and social aspects of their production. Among them, the energy efficiency and the impact on mitigating the emission of greenhouse gases are important issues to consider. Moreover, the monoculture system in large areas, such as sugar cane crop in the state São Paulo, Brazil, has been blamed by social and environmentalists movements as a generator of social inequalities. Ethanol production from cellulose plant tissue, one of the second-generation biofuels, tends to increase the availability of raw materials to energy production and to reduce competition with areas for food production. Despite the advances in fermentation process of structural carbohydrates, improvements are still needed to make the process commercially competitive. It is important that Brazil takes its agricultural potential to quickly enter in this important global energy market.
Keywords: Biofuel; Ethanol; Biodiesel; Environmental and social-economic implications.